Intravenous Ketamine Bolus(es) for the Treatment of Status Epilepticus, Refractory Status Epilepticus, and Cluster Seizures: A Retrospective Study of 15 Dogs - Roynard, Patrick; Bilderback, Ann; Dewey, Curtis Wells (Frontiers in Veterinary Science, 2021)
Status Epilepticus (SE) and cluster seizures (CS) are common occurrences in veterinary neurology, and frequent reasons of admission to veterinary hospitals. With prolonged seizure activity, gamma amino-butyric acid (GABA) receptors (GABAa receptors) become inactive, leading to a state of pharmacoresistance to benzodiazepines and other GABA-ergic medications, refractory status epilepticus (RSE). Prolonged seizure activity is also associated with overexpression of N-methyl-D-aspartic (NMDA) receptors. Rodent models have shown efficacy of ketamine (KET) in treating RSE, and its use has been reported in one canine case of RSE. Boluses of KET 5mg/kg IV have become the preferred treatment for RSE in our hospital. A retrospective study was performed to evaluate and report our experience with the efficacy of KET IV bolus to treat prolonged and/or repeated seizure activity in cases of canine CS, SE and RSE. A total of 15 dogs were retrieved, for 20 hospitalizations and 28 KET IV injections over 3 years. KET IV boluses were used 12 times for RSE (9 generalized seizures, 3 focal seizures) and KET terminated the episode of RSE 12/12 times (100%), however seizures recurred 4/12 times (33%) within ≤6hrs of KET IV bolus. When used for CS apart from episodes of RSE, KET IV bolus was associated with termination of the CS episode only 4/14 times (29%). Only 4/28 (14%) KET IV boluses were associated with adverse effects imputable only to the use of KET. One dog experienced short, self-limited seizure activity during administration of KET IV, which was most likely related to a “premature” use of KET IV (i.e. before GABAergic resistance and NMDA receptors overexpression had taken place). This study indicates that KET 5mg/kg IV bolus may be successful for the treatment of RSE in dogs.